Chemicals Identification in The Ethyl Acetate Fraction and The Antioxidant Activity from Calabash Seed (Cresentia cujete) Extract - Gaspersz, Nelson; Kapelle, Imanuel B. D.; Hattu, Nikmans; Sangadji, Insun; Arpipi, Henderika S. S. (Bogor Agricultural University, Indonesia, 2024)
Calabash (Crescentia cujete) is a plant that grows in tropical climates and is scattered and easily found in Indonesia. Calabash is also known to contain several secondary metabolite compounds that have the potential as an antioxidant. This research is purposed to identify phytochemical compounds in calabash fruit seed extract, identify compounds based on the result of LC-MS, and know the antioxidant activity of calabash fruit seeds. The samples were extracted using the maceration method, and then phytochemical screening, LC-MS tests, and antioxidant tests were continued using the DPPH method. This research showed that the ethanol extract of calabash seed positive contains saponin, flavonoids, and triterpenoid compounds. Ethyl acetate extract of calabash seed contains flavonoids, alkaloids, and triterpenoids. The n-hexane extracts positively contain tannins, alkaloids, and steroids. The values of antioxidant activity of ethanol, ethyl acetate, and n-hexane extracts were IC50 = 29.7883, 7.219, and 848.712 ppm (µg/ml), respectively. Ethyl acetate extract as the best antioxidant activity was then tested with LC-MS, and results obtained from 26 compounds with the composition of the largest % area is convolvidine (11.277%), coumaroylquinic acid (8.290%) and taxchinin G (8,233%). They showed that calabash fruit seed extract has very strong antioxidant activity, with the best activity being the ethyl acetate extract of calabash fruit seed.